Calcium regulation of glucagon-like peptide-1 secretion. - Chua, Sharon Chia Ling. (2010)
Glucagon-like peptide (GLP-1), a hormone secreted from enteroendocrine L-cells in response to nutrient ingestion. Because of its strong potentiating effect on insulin release, GLP-1 now becomes a basis for new class diabetes treatment strategies. However, molecular mechanism of GLP-1 secretion regulation has remained elusive. It is known that GLP-1 secretion is calcium (Ca2+) -dependent but extent of Ca2+ regulation is not established. The aim of this study was to examine the relation between Ca2+ response and GLP-1 secretion and search for the proteins serving as Ca2+ sensors. In β-cells, the identities of Ca2+ sensors only recently started to emerge. Here we tested whether synaptotagmin-2 (Syt2) operates Ca2+ sensing in GLP-1 release by generating Syt2 knockdown (KD) GLUTag cells. We characterized dose-dependence for Ca2+ response to stimulus. For glucose stimulation, GLP-1 secretion reflected the amplitude of Ca2+ increase. In contrast, glutamine had a strong non- Ca2+ dependent component in addition to its Ca2+ -dependent release. Syt2 KD resulted in a reduction of GLP-1 release, however the subcellular localization showed very little co-localization with GLP-1 containing granules. Therefore, Syt2 may directly operate Ca2+ sensing of readily releasable pool of GLP- 1 granules and may also regulate GLP-1 secretion indirectly through regulation of granule trafficking.